Determinants of health- related quality of life (HRQoL) among deaf and hard of hearing adults in Greece: a cross-sectional study - Dialechti Tsimpida; Daphne Kaitelidou; Petros Galanis (BMC, 2018)
Abstract Background Hearing loss is an important public health issue, since it has a very negative impact on peoples' lives, irrespective of the age at which it develops. However, globally there is a noticeable lack of epidemiological data for health outcomes for people who are deaf and hard of hearing. In Greece, people with hearing disabilities are systematically not included in health policy and planning processes, despite there being a marked tendency for global efforts aimed at improving their quality of life. Methods The sample consisted of 140 adults with hearing loss (86 d/Deaf and 54 hard of hearing) and 97 normal hearing as the control group. We run data collection from April to June 2015, using the Greek version of the 36-Item Short Form Health Survey (SF-36v2). Socio-demographic and characteristics about non-medical determinants of health (tobacco and alcohol consumption levels, BMI and physical activity).were also collected and were analysed as possible determinants. Data analysis included bivariate and multivariate analyses such as linear regression models. Results Multivariate analyses identified that in all the SF-36v2 dimensions, the scores among deaf people were lower than those with normal hearing. Determinants included the hearing loss degree, educational level, body mass index, levels of physical activity, and alcohol consumption levels, while the variable "number of family members per household" was inversely associated with physical health summary scale score. Conclusions Improving knowledge of the health-related determinants that affect quality of life for the population with hearing loss is an important step in designing targeted services and interventions. In light of these findings, a special effort must be made to ensure the wellbeing of this population.